PRODUCTION OF COAL ADSORBENTS BY THERMOCHEMICAL METHOD BASED ON COTTON STALKS AND COTTON SHELLS AND THEIR PHYSICAL PROPERTIES - Kuchkarova, Durdona; SOLIYEV , MAHAMMADJON; ERGASHEV , OYBEK (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
This article talks about adsorbents, in particular, activated carbons, which can be a solution to environmental and water pollution, which is the cause of today's urgent problems. Studies on the sources of raw materials for obtaining activated carbon, methods of their activation and advantages of the method are presented based on scientific literature. Methods of obtaining thermochemically activated adsorbents based on cotton stalks and cotton shells, the effect of pyrolysis temperature on the yield of coal formation, chemical activation of the obtained coal samples with alkali, and the physical properties of thermochemically activated adsorbents were studied. Methods of studying dust density and particle sizes and conclusions based on them are presented. The results of the studies show that the increase of the pyrolysis temperature from 300℃ to 500℃ led to a decrease in the yield of the produced coal. Due to the low adsorption property of the formed coal, it was thermochemically activated by chemical activation using alkalis such as NaOH and KOH. During thermochemical activation, its adsorption properties increased.